Gerakan Sosial Petani Pagar Batu - Yuni Puspitasari; Rilus A Kinseng; Saharuddin (Jurnal Sosial Humaniora, 2023)
The emergence of the Pagar Batu peasant social movement can be attributedto the expression of dissent towards companies involved in oil palmplantations. The conversion of agricultural land into these plantations hasposed a myriad of challenges for the peasants. The primary objective of thisstudy was to investigate the underlying issues between the oil palm plantationcompany and the Pagar Batu Peasant community, while also seeking tocomprehend the social movement instigated by the peasants to address theimpact of these plantations. The research was conducted using a qualitativemethod, adopting a case study approach, and gathering primary data throughobservations, in-depth interviews, and focus group discussions, whilesecondary data was obtained from documents and profiles. The researchfindings revealed that the emergence of the social movements primarilyresulted from concerns pertaining to conflicting land ownership,monopolization of palm oil, alterations in land utilization, andtransformations in people's means of livelihood. The Pagar Batu Peasantsopenly conducted their social movements to raise awareness and gainattention, employing various strategies such as demonstrations, landreclamation, and, on certain occasions, resorting to physical confrontation.